FAKTOR-FAKTOR YANG MEMPENGARUHI BELANJA MODAL DI KABUPATEN BOGOR - Rully Farel (Signifikan: Jurnal Ilmu Ekonomi, 2015)
This study is aimed to test the effect of Gross Domestic Regional Product (PDRB) Local Government Revenue (PAD), and Surplus of Budget Financing (SiLPA) on the Capital Expenditure for public service in districts Bogor. The data used are time series data, namely the period 2003 - 2013. Analytical method used is double linear regression or OLS (Ordinary Least Square). The result of this research shows that either altogether or in partial, Gross Domestic Regional Product (PDRB), Local Government Revenue (PAD) and Surplus of Budget Financing (SiLPA) positive and significant impact on capital expenditures in the District Bogor. Variable Surplus of Budget Financing and Local Government Revenue have a considerable influence on capital expenditure. Regression models are made to explain 77.47% of the variance of capital expenditure in District BogorDOI: 10.15408/sjie.v4i2.2305